Analisis Faktor-Faktor yang Mempengaruhi Self-Disclosure di Media Sosial pada Mahasiswa Psikologi Universitas Medan Area - Fortuna, Dewi; Aisyah, Siti (Universitas Medan Area, 2025)
This study aims to analyze the factors that influence self-disclosure on social media in Psychology students at the University of Medan Area. The population in this study were psychology students in 2018 with a total of 350 students. The sample was 66 students with the sampling technique using purposive sampling technique. Data was collected through a scale of self-disclosure factors based on the theory of Devito (2014) including: personality, culture, gender, audience, and topic. The method used in this study was a quantitative method. Data were analyzed using factorial analysis with SPSS version 23. Factorial analysis was used in this study to determine the contribution of each factor that influences self-disclosure on social media in Psychology students at the University of Medan Area. Based on the results of the factor analysis, it shows that each factor has a different contribution. The cultural factor has the highest percentage of 24%, the audience factor has a percentage of 24%, the topic factor is 21%, the personality factor has a percentage of 19%, and the gender factor has a percentage of 12%.